Handbook of neurologic music therapy - Thaut, Michael; Hoemberg, Volker; Abiru, Mutsumi (Oxford University Press, 2014)
A landmark text presenting a new and revolutionary model of music in rehabilitation, therapy and medicine that is scientifically validated and clinically tested. Each of the 20 clinical techniques is described in detail with specific exercises, richly illustrated and with background information regarding research and clinical diagnoses.
Keywords: Music therapy; Neurology